The relationship between cognitive ability and personality scores in selection situations: A meta-analysis - Michael Schilling; Nicolas Becker; Magdalena M. Grabenhorst; Cornelius J. König (International Journal of Selection and Assessment, 2021)
Several faking theories have identified applicants' cognitive ability (CA) as a determinant of faking—the intentional distortion of answers by candidates—but the corresponding empirical findings in the area of personality tests are often ambiguous. Following the assumption that CA is important for faking, we expected applicants with high CA to show higher personality scores in selection situations, leading in this case to significant correlations between CA and personality scores, but not in nonselection situations. This meta-analysis (66~studies, k~=~115 individual samples, N~=~46,265) showed this pattern of results as well as moderation effects for the study design (laboratory vs. field), the response format of the personality test, and the type of CA test.
Keywords: 650; Big Five; cognitive ability; faking; meta-analysis; personality; personnel selection; self-presentation